Isolation and characterisation of carotenoid and genes involved in the carotenoid biosynthetic pathway from ipomoea leaves / Hue Seow Mun - Hue, Seow Mun (2012)
This study focussed on the extraction and characterisation of carotenoid pigments and genes from the carotenoid biosynthetic pathway in I. batatas leaves. Six different local I. batatas varieties were studied namely, I. batatas var. Batu Kelantan (BK), I. batatas var. Batu Biasa (BB), I. batatas var. Oren (Oren), I. batatas var. Indon (Indon), I. batatas var. Vitato (Vitato) and I. batatas var. Biru Putih (BP). The different I. batatas varieties were distinguished based on the morphological variations in their leaves and storage roots. General screening of the β-carotene and lutein levels conducted across the different developmental stages among the different varieties showed that 9 to 12 days old Oren variety leaves exhibited the highest levels of β-carotene and lutein pigments and thus was chosen as the suitable sample for subsequent experiments. Storage at 15°C was found to prolong storage of the leaf samples and the leaves showed a maximum storage of approximately 4 days before the pigments level deteriorated to below 80% of their total amount. Acetone was found to be the suitable extraction solvent due to the higher intensity of yellow colour observed and the presence of higher levels of β-carotene and lutein pigments in the extract. Furthermore, 40% KOH and 2 hours of saponification time were selected as the optimum parameters for extraction. Stability experiments conducted on the yellow pigments extract kept in different storage conditions (temperature, illumination and matrix) for short term and long term durations showed that lutein and β-carotene exhibited lower stability in acetone and upon exposure to high temperature and light. Illumination was found to have had the greater effect on pigment stability compared to temperature. LCMS/MS analysis showed that the yellow extract contained organic acids, lipids and traces of carotenoid, namely β- cryptoxanthin and 4-ketozeaxanthin, besides the two main pigments, β-carotene and lutein. Pesticide analysis conducted via GCMS showed no traces of herbicides, organochlorine insecticide and organophosphorus insecticide in the extract. Antioxidant assays performed on the extract showed that it contained 2.994 ± 0.078 g/ 100g gallic acid equivalents and 114.86 ± 4.35 μg/g catechin equivalents respectively using the Folin-Ciocaltaeu and Vanillin HCl assays. The radical scavenging activity of the extract recorded an IC50 value of 491.86 μg/ml, which was only slightly lower compared to vitamin C (IC50= 471.6 μg/ml). Lycopene epsilon-cyclase (LcyE), lycopene beta-cyclase (LcyB) and phytoene synthase (Psy) genes were successfully isolated from the I. batatas leaves via RT-PCR. Pfam analysis showed that the LcyB and LcyE genes belong to the lycopene cyclase protein family while the Psy gene belongs to the squalene/phytoene synthase domain. BLASTp results on these genes further confirmed their identity and phylogenetic tree revealed their relationship with similar sequences from other plants. This study has shown that I. batatas leaves are suitable source for the extraction of carotenoids with high antioxidant properties.